Frequency of fetal karyotype abnormalities in women undergoing invasive testing in the absence of ultrasound and other high‐risk indications. (18th November 2016) - Ferreira, Jose Carlos P.; Grati, Francesca R.; Bajaj, Komal; Malvestiti, Francesca; Grimi, Maria Beatrice; Trotta, Anna; Liuti, Rosaria; Milani, Silvia; Branca, Lara; Hartman, Jacob; Maggi, Federico; Simoni, Giuseppe; et al.
Abstract: Objectives: No previous studies have reported the frequencies of individual chromosomal anomalies in normal‐appearing fetuses stratified by maternal age (MA) and gestational age (GA). We therefore sought to (1) characterize the frequency of all fetal karyotype anomalies in sonographically normal appearing fetuses without pretest risk factors, and (2) assess MA and GA impact on the proportion of anomalies targeted by screening and consequent impact on residual risk following a negative result. Methods: Fetal karyotypes from samples without prior risk assessment or ultrasound anomalies were analyzed. We calculated, per single‐year MA and in two GA intervals, the predicted frequency of each cytogenetic defect. Results: A total of 129 263 karyotypes were analyzed. The risk for significant, cytogenetically visible chromosomal anomalies, at 15 to 20 weeks GA, varies between 1/301 at MA of 18 years, and 1/9 at MA of 48 years. The proportion of clinically significant anomalies not addressed by current screening methods is 47% at MA of 18 years and 5% at MA of 48 years. Conclusions: By determining frequencies for individual karyotype anomalies stratified by MA and GA, in the setting of normal‐appearing fetuses, a more personalized risk assessment, including the residual risk after a normal fetal aneuploidy screening result, can be provided. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Published data on the prevalence of common aneuploidies are generally based on birth cohort data or referrals for invasive testing based on advanced maternal age and other indications such as abnormal fetal ultrasound or a positive screening test. What does this study add? We present the prenatal frequency of each cytogenetically detectable fetal chromosomal anomaly in women without obvious sonographic abnormalities or other pretest risk factors aside from maternal age (MA). Frequencies reported herein are stratified according to MA and gestational age (GA), the latter of which is relevant to the timing of invasive procedures. We determine that the use of a robust and large prenatal cytogenetic dataset can be used to calculate the proportion of genomic anomalies that would be missed by current screening methods (residual risk after a normal result) in those women presenting without obvious ultrasound anomalies or other risk factors aside from MA.